2014
DOI: 10.1016/j.jse.2014.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of transforming growth factor-β signaling in a rat model of rotator cuff tears

Abstract: Background Muscle atrophy, fatty infiltration, and fibrosis of the muscle have been described as important factors governing outcome after rotator cuff injury and repair. Muscle fibrosis is also thought to have a role in determining muscle compliance at the time of surgery. The transforming growth factor-β (TGF-β) pathways are highly conserved pathways that exert a potent level of control over muscle gene expression and are critical regulators of fibrosis in multiple organ systems. It has been shown that TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 34 publications
(54 reference statements)
1
46
0
Order By: Relevance
“…The near‐significant increase in TGF‐β1 expression seen with LPA treatment may be related to the increase in monocyte‐derived inflammatory cells present in injured muscle. Macrophages are thought to be a key source of TGF‐β1 in chronically injured muscle, and TGF‐β1 signaling has been linked to increased fibrosis within the RC of rats and increased fibrofatty infiltration in mice . Inhibition of TGF‐β1 signaling in mice has likewise shown a reduction in RC muscle atrophy and fibrofatty infiltration by decreasing the number of fibro/adipogenic progenitor cells present in injured muscle .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The near‐significant increase in TGF‐β1 expression seen with LPA treatment may be related to the increase in monocyte‐derived inflammatory cells present in injured muscle. Macrophages are thought to be a key source of TGF‐β1 in chronically injured muscle, and TGF‐β1 signaling has been linked to increased fibrosis within the RC of rats and increased fibrofatty infiltration in mice . Inhibition of TGF‐β1 signaling in mice has likewise shown a reduction in RC muscle atrophy and fibrofatty infiltration by decreasing the number of fibro/adipogenic progenitor cells present in injured muscle .…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen adult female Sprague–Dawley rats underwent complete supraspinatus and infraspinatus tendon transection (TT) with a 5 mm ipsilateral suprascapular nerve resection (DN), as previously described . Sham surgery was performed on the contralateral side of each animal.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that BMP-14 inhibits MMP-13 expression in chondrocytes 21 . In our previous work, we have shown significantly increased TGFβ 22 and BMP 23 signaling in rotator cuff muscles after massive tendon tears, suggesting TGFβ/BMP signaling may be involved in rotator cuff muscle fatty degeneration through regulating MMP-13 expression. Future works are needed to define the role of TGFβ/BMP signaling in regulating MMP-13 in RC muscles.…”
Section: Discussionmentioning
confidence: 89%
“…qRT-PCR was performed to quantify the expression of aSMA 25,26 , Col-1 26 , Col-3 26 , MuRF-1 11,27 , MAFbx 11, 27 , MMP-13 28,29 , PPARg, and SREBP-1 using a Light Cycler 480 SYBR Green I Master kit (Roche Applied Bioscience Inc.). Primer sequences are listed in Table 1.…”
Section: Quantitative Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%